Impact Assessment for Projects on Federal Lands and Outside Canada: The ‘Federal Projects’ Process - Kneen, Jamie (The next generation of impact assessment: a critical review of the Canadian Impact Assessment Act, 2021)
"Legislated impact assessment requirements were first introduced over fifty years ago with the National Environmental Policy Act in the United States and have since spread to over a hundred and fifty jurisdictions around the world. The details have varied widely, reflecting the global diversity of socio-ecological and governance systems and associated issues, traditions, capacities, ambitions, and power structures. In 2015, Canada embarked on a task that no other country has attempted in recent years: fundamentally reconsidering how best to tackle environmental assessment. This review and revision process ended with the passage of the Impact Assessment Act (IAA) in 2019. The Next Generation of Impact Assessment explores the evolution of the Canadian assessment process and evaluates the effectiveness of the IAA."-- Provided by publisher.